Selective Isolation of Newly Synthesized Mammalian mRNA after in Vivo Labeling with 4-Thiouridine or 6-Thioguanosine - Woodford, T.; Schlegel, R.; Pardee, A.B.
Newly synthesized mRNA from hamster cells was labeled in vivo with the thionucleoside analogs 4-thiouridine (4-TU)and 6-thioguanosine (6-TG). The thio-substituted RNA was selectively recovered by Affi-Gel 501 phenylmercury affinity chromatography. Following a l-h labeling period, enrichment for newly transcribed RNA after a single round of chromatography ranged between lo- and 15-fold when compared with total RNA. Exposure of CHO UrdA cells, a uridine auxotrophic line, to 50 pM 4-TLJ allowed for optimal recovery of newly transcribed RNA. Increasing the concentration of 4-TU to 100 pM or labeling with 6-TG at concentrations of 3 FM or greater resulted in similar recoveries from uridine-prototrophic hamster cell lines. For shorter term labeling, exposure of prototrophic cells to 500 fiM 4-TU or 100 pM 6-TG for 15 min allowed newly synthesized RNA to be selectively recovered. As a specific test case, enrichment for histone H3.2 mRNA was analyzed after hamster cells were labeled with 4-TU under conditions in which the gene was highly transcriptionally active. Northern blot analysis and the specific activity of thio-substituted RNA revealed a 15-fold enrichment when compared to total RNA. In vivo labeling of cellular RNA with 4-TU or 6-TG should provide a useful method for studying inducible gene expression and for isolating and cloning specific mRNAs from mammalian cells.
Keywords: CHROMATOGRAPHY; NUCLEIC ACIDS; AFFINITY CHROMATOGRAPHY; RNA ISOLATION; HISTONE MRNA; 4-THIOURIDINE; 6-THIOGUANOSINE